Feasibility of Pulverized Oyster Shell as a Cementing Material - Chou-Fu Liang; Hung-Yu Wang (Advances in Materials Science and Engineering)
This research intends to study the cementing potential of pulverized oyster shell, rich in calcium, when mixed with fly ash and soil. Cylindrical compacted soil and cubic lime specimens with different proportions of the shells and fly ash are made to study the strength variance. Soil, which is classified as CL in the USCS system, commercialized pulverized oyster shell, F-type fly ash, and lime are mixed in different weight percentages. Five sample groups are made to study the compressive strength of soil and lime specimens, respectively. The lime cubes are made with 0.45 W/B ratio and the cylindrical soils are compacted under the standard Procter compaction process with 20% moisture content. The results show that increment of shell quantity result to lower strength on both the soil and lime specimens. In a 56-day curing, the compressive strength of the lime cubes containing fly ash increases evidently while those carrying the shell get little progress in strength. The soil specimens containing fly ash gradually gain strength as curing proceeds. It suggests that mixtures of the shell and fly ash do not process any Pozzolanic reaction nor help to raise the unconfined strength of the compacted soil through the curing.